Ilmu rijal al-hadits: Teori dan ragam penulisan karya rijal al-hadits - Faizeh, Faizeh (Maliki Interdisciplinary Journal, 2024)
The science of Rijalul Hadith is very important in studying the science of Hadith to find out the people who are related in the sanad of a matan. Knowing the narrators of hadiths is very necessary because the narrators of hadiths are relied upon or referred by the hadith pentakhrij to convey a matan. The Rijalul Hadith Science was held because as time goes by, the number of hadith narrators increases, so it is feared that many heresies will emerge. Through the science of Rijalul Hadith, detailed biographies of the narrators can be found.